Implikasi Pengembangan Lembaga Pendidikan Tradisional dan Modern di Pondok Pesantren Al-Ishlahuddiny Kediri Lombok Barat terhadap Relasi Sosial Kemasyarakatan - Burhanudin Burhanudin; Fathurrahman Muhtar; Abdulloh Fuadi (MANAZHIM, 2023)
Education is a process or effort to transfer, preserve and transform cultural values and norms into all aspects and types to the next generation of religion and nation, so that the development of educational institutions becomes the answer to all the demands and needs of the community.The focus of research in writing this thesis is: (1) What is the form of development of traditional educational institutions in Al-Ishlahuddiny Islamic boarding school? (2) What is the form of development of modern educational institutions in al-Ishlahuddiny islamic boarding school? (3) What are the implications of the development of educational institutions on social relations?. The research method used is qualitative method. Data collection techniques through observation, interviews and documentation. Descriptive data analysis techniques by sorting out data, clarifying data, and interpreting data found in the field so that it is easier to draw a conclusion. The results and discussion of this research are (1) Development of traditional educational institutions from the diniyah level to the ma'had level with wetonan, sorogan, memorization and muzakkarah learning methods as well as the curriculum used sourced from classical / traditional books. (2) The development of modern educational institutions from the Ibtidaiyah madrasah level to the tertiary level with lectures, question and answer, and discussion methods as well as the curriculum used is in line with those issued by the Ministry of Education. (3). The implications of the development of such educational institutions are directed at the sections of proselytizing, education and government.